Oxford urdu ka guldasta Gainda grade 2 - Farooqui, Fozia Ahsan (Karachi : Oxford university press, 2023)
"Oxford Urdu Ka Guldasta Gainda (Grade 2)" is a collection of simple and enjoyable Urdu stories, poems, and rhymes designed for second-grade students. The book features engaging content that helps young readers enhance their Urdu language skills, with a focus on vocabulary, comprehension, and basic sentence structures. Through colorful illustrations and fun narratives, it also teaches valuable life lessons and moral values. The stories and poems are crafted to capture the interest of young readers while making learning Urdu an enjoyable experience.
Keywords: Urdu : Textbook